Free language-learning platform for boosting basic english sentence structure among students of tenth grade at EHB Veinticuatro de Julio, Santa Elena. province of Santa Elena. school year 2015-2016. - Perugachi García, Jefferson (2016)
The purpose of the research is focused on the implementation of new strategies for teaching such as the free language-learning platforms to improve Basic English writing. Based on studies done in different countries such as the United States, Guatemala, and East Africa, the author applies the proposal of the academic use of virtual platforms to improve the deficiency in the Basic English sentence structure at escuela de educación básica Veinticuatro de Julio. This work is justified by the results based on observations and tests where students do not reach A2 level in writing according to Common European Framework of Reference for Language, the research methodology was qualitative and quantitative with approaches on action research and grounded theory which leads to enact new educational paths that go hand in hand with the update of learning. The implementation of the free virtual platform benefited the majority of the students. It was obtained positive changes in educational goals in a short-term performance; it is worth mentioning that the research produced good results but also gave standard results which reflect the little interest on the language by the students. It gives emphasis to reformulate ways of teaching and change the traditional teaching for an update in the teachinglearning process where the teachers can use images, videos, or proper use of virtual platforms, encouraging improvement in education and adapting of technology in classes. The content of the virtual platform is suitable for the English book of the tenth grade issued by the Ministry of Education, it contains online activities such as; images, videos, and audios to correct handling and boost the basic English sentence structure. As a result, working with this strategy of teaching will contribute with positive effects on the development of productive skills of the students.